PEMANFAATAN LIMBAH BUAH PISANG DAN AIR KELAPA SEBAGAI BAHAN MEDIA KULTUR JARINGAN ANGGREK BULAN (Phalaenopsis amabilis) TIPE 229 - Ira Djajanegara (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Coconut water and rotten banana fruits are commonly found in traditional markets as organic wastes. One way to overcome the problems caused by these organic wastes is to convert these unuseful matter into an important and economically useful matter by using them as components of tissue culture media. One important commodity that is usually propagated by tissue culture is Phalaenopsis orchid type 229 (Phalaenopsis amabilis). Therefore, it would be more benefit to substitute the expensive chemicals with organic wastes such as coconut water and banana puree.In this experiment, addition of coconut water and banana pure to the minimum media containing commercial fertilizer red Polyhyponex, sucrose and commercial agar did not show any inhibition of Phalaenopsis orchid plantlet growth. This probably caused by sufficient macro and micro nutrients provided by those organic matter and Polyhyponexfertilizer. Moreover, addition of 100 mL/L of coconut water and 100 mg/L banana puree gave the optimum leaf and adventitious shoot formation. On the other hand, addition of 150 mL/L coconut water gave the optimum height and root formation. In this case,growing Phalaenopsis orchid plantlet should be done in 2 subculture period. The first subculture is to obtain maximum amount of leaf and shhot formation while the second subculture is to obtain optimum height and root formation.Key words : Waste, coconut water, banana puree, tissue culture, Phalaenopsis orchi